PERMAINAN TRADISIONAL UTHIK MENDUKUNG PERKEMBANGAN KETERAMPILAN MENGUKUR SATUAN TIDAK BAKU - Qurrotul Ainiyyah; Dini Rakhmawati; Arri Handayani (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstract: Mathematics learning carried out in elementary schools still requires watching and lacks meaning. Learning is carried out only to complete the material by memorizing concepts without understanding how to apply these concepts to everyday life problems. Apart from that, learning mathematics with abstract concepts is considered difficult by students. Meanwhile, for elementary school students, learning will be easier to understand if they have direct experience using concrete objects. Mathematics learning for grade 1 students includes measurement material using non-standard units. In learning, many students are less skilled in taking measurements using non-standard units. From this fact, teachers can carry out learning activities by using concrete objects using traditional uthik games. By conducting learning that incorporates traditional games, students can learn to discover knowledge through their own experiences. Apart from that, traditional games can also enable students to recognize and learn about their cultural riches so they can preserve them. Using the traditional Uthik game in mathematics learning can provide benefits, including providing variations in learning so that it is not monotonous, visualizing abstract mathematical concepts into concrete ones, providing direct learning experiences so that you can develop skills in measuring non-standard units.